The Inside Job or Outside Rule: How Six Governance Forces Shape UK Board Independence? - Qiu, Runmin (Journal of World Economy, 2025)
This research explores how the proportion of independent directors on UK-listed company boards relates to six key institutional dimensions—public participation, political stability, government effectiveness, regulatory quality, rule of law, and anti-corruption control—drawing on agency theory and resource dependence perspectives. Using panel data from non-financial firms listed on the London Stock Exchange (2013-2023), we extract independent director ratios from annual reports and combine them with the World Bank’s Global Governance Indicators to quantify institutional quality. Our analysis employs double fixed-effects regression models and other techniques to effectively control for time and firm-specific heterogeneity. These findings reveal that while political stability significantly encourages the appointment of independent directors, the other five institutional dimensions show strong negative substitution effects. Notably, these institutional responses show no significant variation across firms of different sizes. Based on these results, the paper proposes a novel, integrated framework for board independence within a multi-dimensional regulatory system. Importantly, feasible decision-making references for investors to optimize governance risk assessment, corporate executives to adjust board composition, and regulatory authorities and industry associations to synchronously improve governance guidelines and information disclosure. In summary, this paper contributes uniquely by constructing a comprehensive multi-dimensional governance framework, integrating six distinct forces, and demonstrating how their interplay—particularly between regulatory enforcement and investor incentives—generates non-linear impacts on board independence.